Assessing the influence of demographic factors on online selling engagement in the Philippines the moderating roles of ease of entry, flexibility, and autonomy preference - Jagunos, Johanna Mae M.; Olmida, Kaye Anne C.; Remandaban, Johanna Mariae F.
Online selling has been widely utilized and adopted in the Philippines. Today, a majority of online selling platforms are subject to increasing regulation by the government. However, most existing literature typically focuses on the consumer perspective, leaving the seller's experiences and motivations underexplored. Recognizing this gap, this study investigates how demographic factors, specifically age, sex, education, income, and marital status, influence engagement in online selling in the Philippines. Grounded in the Theory of Planned Behavior, the research also examines how two key moderating variables, Ease of Entry (EE) and Flexibility and Autonomy Preference (FA), alter the relationship between demographic characteristics and online selling engagement (OSE). Using a quantitative approach, the researchers conducted a survey with 103 online sellers from platforms such as Facebook Marketplace, Shopee, and Tik Tok Shop. Statistical techniques including reliability analysis, factor analysis, and multiple regression were employed to analyze the data. Findings show that younger, single, and more educated individuals are more likely to engage in online selling. Additionally, EE and FA significantly moderate these relationships; for instance, high EE increases the likelihood of participation among lower-income individuals, while strong FA preferences amplify involvement among women and youth. This study contributes valuable insights into the socio-economic dynamics of digital entrepreneurship in the Philippines and informs platform design, policy development, and support programs tailored to diverse seller profiles.